Valve‐in‐valve implantation of a novel and small self‐expandable transcatheter heart valve in degenerated small surgical bioprostheses: The Hamburg experience. Issue 3 (20th May 2014) - Diemert, Patrick; Seiffert, Moritz; Frerker, Christian; Thielsen, Thomas; Kreidel, Felix; Bader, Ralf; Schirmer, Johannes; Conradi, Lenard; Koschyk, Dietmar; Schnabel, Renate; Reichenspurner, Hermann; Blankenberg, Stefan; et al.
<x xml:space="preserve">Abstract</x> Background Transcatheter valve‐in‐valve (VIV) implantation has emerged as a novel treatment option in patients with degenerated aortic bioprostheses and high surgical risk. However, VIV implantation in small aortic bioprostheses using first generation TAVI devices has frequently resulted in high postprocedural gradients and small effective orifice areas. Recently, an updated version of the self‐expandable Medtronic CoreValve prosthesis, which is particularly suitable for small aortic annuli, has become available. We report on the feasibility and early results of VIV implantation using this novel device in a series of patients with degenerated small aortic bioprostheses. Methods and Results 16 patients from two Hamburg hospitals (age range 72–92 years) underwent implantation of a 23‐mm CoreValve Evolut (Medtronic, Minneapolis, MN, USA) transcatheter heart valve into failing aortic bioprostheses with internal diameters below 21 mm. All patients were considered high risk for surgical aortic valve replacement after evaluation by an interdisciplinary heart team mean (logistic EuroSCORE range 9.0–88%). Implantation was successful without relevant remaining aortic regurgitation or signs of stenosis and a marked reduction in postprocedural gradientswas observed in 14 out of 16 patients. The mean gradient was reduced from from 34 mm Hg (SEM 10 mm Hg) to 14 mm Hg (SEM 6 mm Hg). No major device‐ or procedure‐related adverse events occurred during 30‐day follow up and clinical improvement was observed. Conclusions Failing aortic bioprostheses with small internal diameters continue to be a challenging pathology for TAVI due to the risk of high residual gradients and small aortic orifice areas. This report provides first evidence that the 23‐mm CoreValve Evolut, a novel self‐expanding prosthesis, provides an improved treatment option in these specific patients due to its low profile which resulted in promising early results. © 2013 Wiley Periodicals, Inc.